2015
DOI: 10.1371/journal.pone.0122931
|View full text |Cite
|
Sign up to set email alerts
|

Probing ADAMTS13 Substrate Specificity using Phage Display

Abstract: Von Willebrand factor (VWF) is a large, multimeric protein that regulates hemostasis by tethering platelets to the subendothelial matrix at sites of vascular damage. The procoagulant activity of plasma VWF correlates with the length of VWF multimers, which is proteolytically controlled by the metalloprotease ADAMTS13. To probe ADAMTS13 substrate specificity, we created phage display libraries containing randomly mutated residues of a minimal ADAMTS13 substrate fragment of VWF, termed VWF73. The libraries were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…S1). This concurs with previous studies of substrate specificity of ADAMTS‐13, in which the substitution of Tyr1605 to lysine did not abolish the proteolysis of a VWF73 expressing phage 29, 30. Our findings suggest proteolysis of fibrinogen by GoF ADAMTS‐13 will be less efficient than its cleavage of unfolded VWF.…”
Section: Discussionsupporting
confidence: 92%
“…S1). This concurs with previous studies of substrate specificity of ADAMTS‐13, in which the substitution of Tyr1605 to lysine did not abolish the proteolysis of a VWF73 expressing phage 29, 30. Our findings suggest proteolysis of fibrinogen by GoF ADAMTS‐13 will be less efficient than its cleavage of unfolded VWF.…”
Section: Discussionsupporting
confidence: 92%
“…The apparent pseudo-first-order rate constant, k app , calculated for WT VWF73 within the library, was 0.2888 ± 0.001, yielding a k cat /K M value of 5.78 × 10 7 M −1 ·min −1 (SI Appendix, Fig. S5), which is comparable to the value determined for the recombinant WT VWF73 peptide (Table 2) (26)(27)(28).…”
Section: High-throughput Sequencing Of Uncleaved Phages Defines the Psupporting
confidence: 54%
“…Segment A, spanning Pro6-Val12 of VWF73, includes the Tyr10-Met11 scissile bond and showed the greatest enrichment of mutation frequency. Segment B spans Asp19-Asp27 and contains Ile21, a previously identified exosite-binding residue (26). Segment C spans Pro53-Leu69 and contains a number of residues exhibiting mutation enrichment after selection (Fig.…”
Section: High-throughput Sequencing Of Uncleaved Phages Defines the Pmentioning
confidence: 97%
“…Promiscuity may therefore be expected. The entire range of possible residue changes that permit proteolysis of the small VWF substrate VWF73 has been mapped by use of a substrate phage display library . This has highlighted the importance of the scissile bond residues as well as previously identified exosite regions (see below), but has also demonstrated that, within these regions, many possible residue substitutions that permit cleavage are possible.…”
Section: Conformational Activation Of Adamts‐13 By Vwfmentioning
confidence: 99%